Raumplanung - Instrument der Obrigkeitsstaatlichkeit oder Instrument einer demokratischen Kulturlandschaftsgestaltung? - Priebs, Axel (ERDKUNDE, 2000)
Spatial planning - instrument of blind faith in authority or instrument of democratic development of European cultural landscape? This paper is a response to the statements of HOLZNER published in this issue. The author cannot agree with HOLZNER's attitude towards German spatial planning in which HOLZNER recognizes strong tendencies for a blind faith in authority. In the author's estimation it is not justified to make a direct connection between the Third Reich ideology and public influence on land use and housing development today. On the contrary, the author is convinced that spatial planning is an unpopular but necessary instrument of a democratic society which has realized that natural resources are limited and which has decided upon a sustainable use of space. The author sees some challenges which spatial planning and planning politicians have to accept (e.g. diversifying life styles, changing housing preferences and an increased importance of post-suburban neighbourhoods). The development control by binding plans must be supplemented by extended use of market forces and contract solutions. Though the freedom of the individual has it limits where it restricts the quality of life of other individuals or causes economic or ecological damage. The preserving of European cultural landscapes and of the European city is a primary political goal not only in Germany. To achieve this goal, spatial planning can make an important contribution.